ON A LIPSCHITZ STABILITY PROBLEM FOR p-LAPLACIAN BESSEL EQUATION - Gulsen, Tuba; Yilmaz, Emrah; Panakhov, E. S. (Ankara Univ, Fac Sci, 2017)
In this study, we are enunciative of some asymptotic expansions and reconstruction formulas for inverse nodal problem of p-Laplacian Bessel equation. Furthermore, Lipschitz stability problem for this equation with Dirichlet boundary conditions is solved. And, it is also proved that the space of all potential functions w is homeomorphic to the partition set of all asymptotically equivalent nodal sequences induced by an equivalence relation.
Keywords: p-Laplacian Bessel equation; Inverse nodal problem; Lipschitz stability